Functional group influences on the reactive azo dye decolorization performance by electrochemical oxidation and electro-Fenton technologies - da Costa Soares, Izabelle Cristina; da Silva, Djalma Ribeiro; do Nascimento, José Heriberto Oliveira; Garcia-Segura, Sergi; Martínez-Huitle, Carlos Alberto [UNESP] (Springer Nature, 2017)
Electrochemical water treatment technologies are highly promising to achieve complete decolorization of dyebath effluents, as demonstrated by several studies reported in the literature. However, these works are focused on the treatment of one model pollutant and generalize the performances of the processes which are not transposable since they depend on the pollutant treated. Thus, in the present study, we evaluate, for the first time, the influence of different functional groups that modify the dye structure on the electrochemical process decolorization performance. The textile azo dyes Reactive Orange 16, Reactive Violet 4, Reactive Red 228, and Reactive Black 5 have been selected because they present the same molecular basis structure with different functional groups. The results demonstrate that the functional groups that reduce the nucleophilicity of the pollutant hinder the electrophilic attack of electrogenerated hydroxyl radical. Thereby, the overall decolorization efficiency is consequently reduced as well as the decolorization rate. Moreover, the presence of an additional chromophore azo bond in the molecule enhances the recalcitrant character of the azo dyes as pollutants. The formation of a larger and more stable conjugated π system increases the activation energy required for the electrophyilic attack of •OH, affecting the performance of electrochemical technologies on effluent decolorization.
Keywords: Boron-doped diamond anode; Electro-Fenton; Electrochemical advanced oxidation processes; Reactive azo dyes; Wastewater treatment